Processos de degradação, recuperação e reabilitação de áreas mineradas: elaboração de um plano para desenvolvimento de área referência em recuperação e reabilitação de área pós-minerada em extração de areia no Vale do Paraíba - ALMEIDA, Thatiane Reis (2019)
Mineral resources are increasingly essential to mankind, but this subject turns to be a dilemma, whereas mining is taken as a polluting and devastating activity to the environment. The solution to this dilemma is the implementation of a new mining profile, where there is respect for the environment and future generations, and that is possible the practice of sustainable mining reconciling economic development and environmental preservation. The present study intends to report on the mining extraction and the consequences to the environmental in order to propose a reference for scientific and cultural about recovering and rehabilitation post-mined areas of sand extraction in the floodplain of Rio Paraíba do Sul. The methods consisted on the evaluation and analysis of extraction process, evaluation of the use and natural vegetation recovery of degraded area. The conclusions of the evaluation of the use and natural vegetation cover at the area of study, was very satisfactory, accounting and reporting the environmental consequences suffered in the study area, since the beginning of the period studied. Thus confirming the visionary idea of settling a reference center to post-mined area at Vale do Paraíba.